Effects of Pharmacotherapy on Combat-Related PTSD, Anxiety, and Depression: A Systematic Review and Meta-Regression Analysis. - Timothy W Puetz; Shawn D Youngstedt; Matthew P Herring (PLoS ONE, 2015)
Objectives To estimate the effect of pharmacotherapy on PTSD, anxiety, and depression among combat veterans; to determine whether the effects varied according to patient and intervention characteristics; and to examine differential effects of pharmacotherapy on outcomes. Materials and methods Google Scholar, PILOTS, PsycINFO, PubMed, and Web of Science databases were searched through November 2014. Searches resulted in eighteen double-blind, placebo controlled trials of 773 combat veterans diagnosed with PTSD and included only validated pre- and post-intervention PTSD and anxiety or depression measures. Authors extracted data on effect sizes, moderators, and study quality. Hedges' d effect sizes were computed and random effects models estimated sampling error and population variance. The Johnson-Neyman procedure identified the critical points in significant interactions to define regions of significance. Results Pharmacotherapy significantly reduced (Δ, 95%CI) PTSD (0.38, 0.23-0.52), anxiety (0.42, 0.30-0.54), and depressive symptoms (0.52, 0.35-0.70). The effects of SSRIs and tricyclic antidepressants on PTSD were greater than other medications independent of treatment duration. The effect of SSRIs and tricyclic antidepressants were greater than other medications up to 5.2 and 13.6 weeks for anxiety and depression, respectively. The magnitude of the effect of pharmacotherapy on concurrently-measured PTSD, anxiety, and depression did not significantly differ. Conclusions Pharmacotherapy reduced PTSD, anxiety, and depressive symptoms in combat veterans. The effects of SSRIs and tricyclic antidepressants were greater for PTSD and occurred quicker for anxiety and depression than other medications.